Leadership Styles and Their Impact on Organizational Performance in the Office of the Minister Of State, Governor of Dhofar in the Sultanate of Oman: Organizational Culture as a Mediating Variable - Khalid Ghanim Mohammed Alkathiri; Mohamed Mihlar Abdul Muthaliff; Ali Nasser Ali Al-Tahitah (OCERINT International Organization Center of Academic Research, 2024)
Non-Indexed Publication